K voprosu projavlenija reakcij anticipacij v bokse - Akopjan, A. O.; Kulagina, L. A.; Domuladžanova, O. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
In the article various manifestations of complex visual-motor reactions in boxing are discussed, including the reactions of anticipation of possible attacking and counter-attacking actions of the boxer. The technique and results of experimental studies with female boxers of high class are presented, in which the interrelations of the visual motor reactions of various boxer psychotypes are revealed.